An academic exchange between JCW Ahiakpor and F Gerits - Grilli, Matteo (Southern Journal for Contemporary History, 2022)
We do not see very often one of our articles sparking a debate in the pages of our journal. However, we welcome this occurrence. In this case, Frank Gerits’ article in the latest issue of the Southern Journal for Contemporary History - which analyses the economic history of Ghana vis-à-vis the economic and political thought of important Ghanaian economists - has provoked a critical response from one of the intellectuals cited by Gerits himself: JCW Ahiakpor.